1987
DOI: 10.1530/acta.0.1150067
|View full text |Cite
|
Sign up to set email alerts
|

Elevated anti-α-galactosyl antibody titres. A marker of progression in autoimmune thyroid disorders and in endocrine ophthalmopathy?

Abstract: Abstract. The titres of anti-α-galactosyl antibodies were measured by passive haemagglutination in 50 control subjects and in 128 patients presenting with various thyroid disorders. Titres of control subjects ranged from 1/10 to 1/80, regardless of age and blood group. Elevated titres (> 1/80) were constantly noted in 6/6 patients with progressive exophthalmos, in 5/5 patients with untreated Graves' disease, and in 11/12 patients with progressive nontoxic goitre. By contrast, the titres were within the norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…These authors suggested that previous thyroid lesions could expose normally hidden antigenic determinants that would in turn enhance the antigal response, as described to occur after some renal injuries (32). Interestingly, the reactivity pattern of the antigal reactive human thyroid cells obtained by Etienne-Decerf (30) was dotted fluorescence on the cell surface similar to that observed by us in cells reactive with chagasic antigal (Fig. 3a).…”
Section: Hypothesis About Origin Of Antigal Reactive Epitopessupporting
confidence: 68%
See 1 more Smart Citation
“…These authors suggested that previous thyroid lesions could expose normally hidden antigenic determinants that would in turn enhance the antigal response, as described to occur after some renal injuries (32). Interestingly, the reactivity pattern of the antigal reactive human thyroid cells obtained by Etienne-Decerf (30) was dotted fluorescence on the cell surface similar to that observed by us in cells reactive with chagasic antigal (Fig. 3a).…”
Section: Hypothesis About Origin Of Antigal Reactive Epitopessupporting
confidence: 68%
“…These authors suggested that antigal antibodies may be implicated in the elimination of "altered" human red blood cells. Etienne-Decerf (30) showed that 30% of human thyroid cells, obtained from thyroid primary cultures and treated in vitro with exogenous trypsin, reacted with antigal antibodies. These authors suggested that previous thyroid lesions could expose normally hidden antigenic determinants that would in turn enhance the antigal response, as described to occur after some renal injuries (32).…”
Section: Hypothesis About Origin Of Antigal Reactive Epitopesmentioning
confidence: 99%
“…Anti-Gal's blocking ofACP activation may serve to protect man from continuous activation of complement on the surface ofthese and potentially other senescent human cells. Conversely, anti-Gal appears to play a detrimental role in the pathogenesis of certain autoimmune disorders, including thyroiditis, IgA nephropathy, and HenochShoenlein purpura (16,47). Our findings suggest that anti-Gal also may play a role in the intravascular survival of certain Gram-negative bacteria and raise intriguing questions about the effect ofthis ubiquitous molecule on other immune effector mechanisms, including opsonophagocytosis and T and B cellmediated events.…”
Section: Discussionmentioning
confidence: 99%
“…Such antibodies mimic the effect of TSH and continuously stimulate the metabolic activity of thyroid cells, leading to enlargement of the thyroid and hyperactivity of the gland (thyrotoxicosis). Anti-Gal titers were found to be markedly elevated in such patients [24], possibly as a result of the aberrant expression of ~-galactosyl epitopes on autologous thyroid cells. Furthermore, if these epitopes are expressed on the TSH receptor glycoprotein molecules, one could predict that the binding of anti-Gal would result in a stimulatory TSH-like effect.…”
Section: Anti-gal and Autoimmune Diseasesmentioning
confidence: 97%
“…Analysis of the anti-Gal isotypes in the serum was performed using specific anti-isotype antibodies [16,24,32,68]. These studies have indicated that most of the anti-Gal reactivity in the serum is of IgG class.…”
Section: Anti-gal Interaction With Synthetic Oligosaccharidesmentioning
confidence: 99%